Environmental education in primary schools: a case study with plastic resources and recycling. Issue 6 (18th August 2019) - So, Winnie Wing Mui; Chow, Stephen Cheuk Fai
ABSTRACT: This paper aims to examine teachers' use of strategies and approaches in integrating Plastic Resources Education (PRE) into primary school life in order to overcome the challenges encountered during implementation to promote environmentally friendly practices. Case studies with eight Hong Kong teachers from PRE-participating primary schools were invited to take part in focus group interviews, to explicate their personal stories and experiences associated with the PRE implementation in primary schools. Based on the data collected from the teachers' sharing, several challenges which are commonly reported in the previous literature, including lack of time, shortage of manpower, and insufficient pupil engagement were found. The teachers tackled the barriers by using different strategies to improve pupils' involvement as well as getting support from the relevant stakeholders of school management and parents. The case studies provide crucial and relevant information which can be used as a reference for other schools to integrate PRE more efficiently to facilitate learning.